A spatial assessment of potential biomass for bioenergy in Australia in 2010, and possible expansion by 2030 and 2050. Issue 4 (10th January 2016) - Crawford, Debbie F.; O'Connor, Michael H.; Jovanovic, Tom; Herr, Alexander; Raison, Robert John; O'Connell, Deborah A.; Baynes, Tim
Abstract: This paper provides spatial estimates of potentially available biomass for bioenergy in Australia in 2010, 2030 and 2050 (under clearly stated assumptions) for the following biomass sources: crop stubble, native grasses, pulpwood and residues (created either during forest harvesting or wood processing) from plantations and native forests, bagasse, organic municipal solid waste and new short‐rotation tree crops. For each biomass type, we estimated annual potential availability at the finest scale possible with readily accessible data, and then aggregated to make estimates for each of 60 Statistical Divisions (administrative areas) across Australia. The potentially available lignocellulosic biomass is estimated at approximately 80 Mt per year, with the major contributors of crop stubble (27.7 Mt per year), grasses (19.7 Mt per year) and forest plantations (10.9 Mt per year). Over the next 20–40 years, total potentially available biomass could increase to 100–115 Mt per year, with new plantings of short‐rotation trees being the major source of the increase (14.7 Mt per year by 2030 and 29.3 Mt per year by 2050). We exclude oilseeds, algae and 'regrowth', that is woody vegetation naturally regenerating on previously cleared land, which may be important in several regions of Australia ( Australian Forestry 77, 2014, 1; Global Change Biology Bioenergy 7, 2015, 497). We briefly discuss some of the challenges to providing a reliable and sustainable supply of the large amounts of biomass required to build a bioenergy industry of significant scale. More detailed regional analyses, including of the costs of delivered biomass, logistics and economics of harvest, transport and storage, competing markets for biomass and a full assessment of the sustainability of production are needed to underpin investment in specific conversion facilities (e.g. Opportunities for forest bioenergy: An assessment of the environmental and economic opportunities and constraints associated with bioenergy production from biomass resources in two prospective regions of Australia, 2011a).